Photonic asynchronous delta-sigma modulator system for analog-to-digital conversion - Siahmakoun, Azad (2012)
A novel photonic asynchronous delta-sigma modulator (ADSM) has been investigated and demonstrated for the first time in this article. An inverted bistable quantizer is required due to use of a positive feedback in this noninterferometric optical implementation. The principles of the proposed optical first-order and second-order ADSM are modeled and analyzed. Two main components of the novel optical ADSM; the leaky integrator and the inverted bistable quantizer have been mathematically analyzed, simulated, and characterized. Finally, a prototype fiber-optic ADSM is constructed. The prototype operates at MHz frequencies producing four effective-number-of-bits resolution. The reported fiber-optic ADSM is a very promising for future integration of this system on a photonic chip thus increasing the operation frequency range up to tens of GHz.